Integration of SiC-1D nanostructures into nano-field effect transistors. (January 2015) - Ollivier, M.; Latu-Romain, L.; Salem, B.; Fradetal, L.; Brouzet, V.; Choi, J.-H.; Bano, E.
Abstract: We report on the integration and the electrical transport properties of silicon carbide-based one-dimensional nanostructures into field effect transistors. Different kinds of SiC-based 1D nanostructures have been used: 3C– and 4H–SiC nanowires obtained by a plasma etching process, Si–SiC core–shell nanowires and SiC nanotubes both obtained by a carburization route of silicon nanowires.